Soft Skill and Hard Skill Development Model in Improving the Quality of Human Resources in the Higher Education Environment - Marzuki, Sitti Nikmah; Muljan, Muljan; Haslinda, Haslinda; Affandi, Lukman (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
This research aims to identify the soft and hard skills students need to improve the quality of human resources in the tertiary environment. The research was conducted in Bone Regency, focusing on IAIN Bone students and related stakeholders. The research method used is qualitative research, which involves interviews, observations, and questionnaires to collect primary data and documents and literature as secondary data. Data analysis was carried out using qualitative descriptive techniques and descriptive statistical analysis. It is hoped that the results of this research will be able to design practical and applicable skills development models and evaluate the effectiveness of the skills development programs that have been implemented. The ultimate goal of this research is to improve the quality of college graduates so that they are ready to compete in the world of work, support higher education policies, increase the competitiveness of universities, and prepare students to face increasingly complex future challenges. This research provides recommendations to universities regarding developing curricula and learning programs that are more comprehensive and relevant to industry needs.